Removal of Hexavalent Chromium from Aqueous Solutions by Adsorption on Thermally Modified and Non-Modified Eggshells (Journal of Engineering, 2013)
Removal of heavy metals from waste water has received a great deal of attention. The compare Cr(VI) adsorption characteristics removing from wastewater by using thermally modified and non-modifiedeggshells were examined